Finding the right mix: teaching methods as predictors for student progress on learning objectives - Glover, Jacob I. (Kansas State University, 2012)
This study extends existing student ratings research by exploring how teaching methods, individually and collectively, influence a minimum standard of student achievement on learning objectives and how class size impacts this influence. Twenty teaching methods were used to predict substantial or exceptional progress on each of 12 learning objectives. Analyses were conducted in four class-size groups, Small (between 10-14 students), Medium (between 15-34 students), Large (between 35-49 students), and Very Large (50 or more students). Archival data were over 580,000 classes of instructors and students who responded to two instruments within the IDEA Student Rating of Instruction system: Instructors completed the Faculty Information Form, and students responded to the Student Ratings Diagnostic Form. Significant progress, for the purpose of this study, means students indicated they made either substantial or exceptional progress on learning objectives the instructor identified as relevant to the course. Therefore, student ratings of progress were dichotomized and binary logistic regression was conducted on the dummy variables. Descriptive statistics and point-biserial correlations were also conducted to test the hypotheses. Teaching methods that stimulated student interest were found to be among the strongest predictors of significant progress on the majority of learning objectives across all class sizes. For all class sizes, significant progress was correctly classified from a low of 76% of the time to a high of 90% of the time. The higher students rated the instructor in stimulating them to intellectual effort the more progress they reported on a majority of learning objectives across all class sizes. Higher instructor ratings on inspiring students to set and achieve challenging goals were also associated with significant student progress on learning objectives across all class sizes. Class size was not a major factor affecting the predictive strength of groups of teaching methods on student progress on learning objectives. However, it was a factor concerning the predictive strength of individual teaching methods. The larger the enrollment the greater was the predictive strength of key teaching methods. Implications of the study for faculty professional development and for future research are discussed.
Keywords: Course evaluations; Teaching methods; Learning objectives; Educational evaluation (0443); Higher Education (0745)